Temporal patterns of entomopathogenic nematodes in Florida citrus orchards: Evidence of natural regulation by microorganisms and nematode competitors. (January 2019) - Campos-Herrera, Raquel; Stuart, Robin J.; Pathak, Ekta; El-Borai, Fahiem E.; Duncan, Larry W.
Abstract: The abundance of three entomopathogenic nematode (EPN) species, seven species of nematophagous fungi, free living nematode competitors of EPNs and a bacterial ectoparasite of EPNs were monitored during approximately two years in four Florida citrus orchards. The objective of the surveys was to identify natural enemies that potentially regulate the temporal abundance of naturally occurring EPNs by using molecular tools. Nematodes were extracted from two soil depths at ∼ monthly intervals, DNA extracted, and target organisms were measured using qPCR. Potentially causal relationships between the temporal patterns of EPNs and their natural enemies were assessed primarily with stepwise regression of variables at various time lags. Drechslerella dactyloides was the only nematophagous fungus species exhibiting evidence of top-down regulation, being inversely related to population change of Heterorhabditis indica at two of three sites. Acrobeloides spp. (EPN competitors) were associated with reduced population growth of Steinernema diaprepesi at two sites and H. indica was associated with reduced abundance of H. zealandica and S. diaprepesi at one site each. A Paenibacillus sp. exhibited significant phase-space, predator-prey dynamics at two of three sites with abundant S. diaprepesi, a species-specific host of the bacterium. The initial abundance of both S. diaprepesi and Paenibacillus sp. explained significant variability in population changes of S. diaprepesi in a multiple regression model at a lag of three months. Controlled experiments showed that pH is directly related to adherence of the bacterial endospores to the S. diaprepesi cuticle. Soil pH in these surveys was directly related to the infestation rate (encumbrance) by Paenibacillus and inversely related to the abundance of S. diaprepesi . Vertical distribution patterns reflected potential routes for avoiding competition and predation between species. Nematode-trapping fungi tended to inhabit shallower soil horizons than did several other nematophagous fungal species and S. diaprepesi and H. indica . The nematophagous fungus Purpureocillium lilacinum was especially abundant in deeper soil horizons and in the flatwoods sites. Depth distribution among EPNs also differed significantly with H. indica  >  S. diaprepesi  > than H. zealandica . These results support soil pH management to conserve the demonstrated services of S. diaprepesi . They also suggest a need to better understand potential non-target effects of practices favorable to nematophagous fungi and bactivorous nematode competitors of EPNs. Graphical abstract: Image 1 Highlights: Entomopathogenic nematode (EPN) populations measured for 2 years at 4 sites. EPN population flux inversely associated free living nematode competitors. EPN and phoretic bacteria exhibited phase-space, predator prey dynamics. Soil pH regulated bacteria endospore adherence to nematode cuticle.